Isopenicillin N synthase binds δ-(L-α-aminoadipoyl)-L-cysteinyl-D-thia-allo-isoleucine through both sulfur atoms. - Clifton, I; Ge, W; Adlington, R; Baldwin, J; Rutledge, P (2011)
Isopenicillin N synthase (IPNS) catalyses the synthesis of isopenicillin N (IPN), the biosynthetic precursor to penicillin and cephalosporin antibiotics. IPNS is a non-heme iron(II) oxidase that mediates the oxidative cyclisation of the tripeptide δ-L-α-aminoadipoyl-L-cysteinyl-D-valine (ACV) to IPN with a concomitant reduction of molecular oxygen to water. Solution-phase incubation experiments have shown that, although IPNS can turn over analogues with a diverse range of hydrocarbon side chains in the third (valinyl) position of its substrate, the enzyme is much less tolerant of polar residues in this position. Thus, although IPNS converts δ-L-α-aminoadipoyl-L-cysteinyl-D-isoleucine (ACI) and AC-D-allo-isoleucine (ACaI) to penam products, the isosteric sulfur-containing peptides AC-D-thiaisoleucine (ACtI) and AC-D-thia-allo-isoleucine (ACtaI) are not turned over. To determine why these peptides are not substrates, we crystallized ACtaI with IPNS. We report the synthesis of ACtaI and the crystal structure of the IPNS:Fe(II) :ACtaI complex to 1.79 Å resolution. This structure reveals direct ligation of the thioether side chain to iron: the sulfide sulfur sits 2.66 Å from the metal, squarely in the oxygen binding site. This result articulates a structural basis for the failure of IPNS to turn over these substrates.